The Impact of FX Exposure on the Firm's Stock Market Return - Mariia Bondarenko; Karel Brůna (European Financial and Accounting Journal, 2021)
It is generally acknowledged that one of the risks faced by any company is FX risk, especially when the business operates internationally. For individual companies, exposure to FX risk results in different financial implications, stressing such parameters as the industry affiliation and the company's size with respect to the level of FX risk exposure. In this paper we analyse how FX exposure of companies of different size and operating in industrial and service sectors affects their stock market returns. Using the panel regression with macroeconomic and companies' specific factors for 208 European companies analysed over the period 2012-2018, we show that the link between changes in the exchange rate and the stock return is statistically significant and that medium-size companies as well as firms operating in the service sector of economy are more exposed to this impact.
Keywords: F31; G12; G32; 650; Stock return; Stock price; Exchange rate; FX exposure; FX risk